INDEKS KUNING TELUR (IKT) DAN Haugh Unit (HU) TELUR ITIK LOKAL DARI BEBERAPA TEMPAT BUDIDAYA ITIK DI JAWA - Alfiyah, Yeni; Praseno, Koen; Mardiati, Siti Muflichatun (BULETIN ANATOMI DAN FISIOLOGI dh SELLULA, 2015)
One of the effort to increase the duck support to egg production was necessary to consideration some factors. One of the factor was feed. Parameter to determined egg quality  namely : yolk index, and haught unit (HU). IKT (Yolk Index) was a comparison between yolk and yolk diameter. Whereas HU was a quality parameter of egg freshness which was numbered based on the high of albumen and egg weight. The aim of this research was to  know the yolk index and Haugh Unit. The local egg duck from some culture place in Java and to know the management from each place as knowledge to duck farmer to optimalized  the management duck culture. The sample was got from four place culturing in Java, namely Kroya Cirebon Village (A), Pasar Bawang Brebes Village (B), Kalijoso Magelang Village (C), dan Modopuro Mojokerto Village (D), each of them 20 eggs. The Methode which used in this research was with egg measurement the parameter, such as measurement the weight duck, egg weight, albumen high, yolk hight, yolk diameter. The measurement of IKT and HU was done in structure and function of animal biology laboratory. The research design that be used was Completely Randomozed Design with SAS programme. The product of IKT and HU from four culturing duck place in Java were different, IKT has range rata (A) 0.419, (B) 0.463, (C) 0.482, and (D) 0.492. whereas the range of  HU value were A) 86.93, (B) 97.53, (C) 100.33, (D) 99.45. this was caused by the difference of management from kind of feed offering, the management that can choosed to applied for other duck farmer, such as from the duck farmer from Modopuro Mojokerto Village and Kalijoso Magelang Village.   Keywords: The Duck, Yolk Index, Haugh Unit